-5\(^x\) + (-4) . 5\(^{x+4}\) - 3 . 5\(^{x+4}\) = 2. 5\(^{11}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a,Cách 1: (6/11 + 5/11 ) x 3/7 Cách 2 :(6/11 + 5/11) x 3/7
= 1 x 3/7 =6/11 x 3/7 + 5/11 x 3/7
= 3/7 = 18/77 + 15/77
= 3/7
b, Cách 1:3/5 x 7/9 - 3/5 x 2/9 Cách 2 :3/5 x 7/9 - 3/5 x 2/9
= 7/15 - 2/15 = 3/5 x (7/9 - 2/9 )
= 1/3 = 3/5 x 5/9
= 1/3
c, Cách 1:(6/7 - 4/7) : 2/5 Cách 2: ( 6/7- 4/7 ) : 2/5
= 2/7 : 2/5 = 6/7 : 2/5 - 4/7 : 2/5
= 5/7 = 15/7 - 10/7
= 5/7
d,Cách 1:8/15 : 2/11 + 7/15 : 2/11 Cách 2:8/15 : 2/11 +7/15 : 2/11
= 88/30 + 77/30 =(8/15+7/15) :2/11
= 11/2 = 1 : 2/11
= 11/2
Bài 2 cậu tự làm nhé !
a: =>x-2/5=3/4:1/3=3/4*3=9/4
=>x=9/4+2/5=45/20+8/20=53/20
b: =>x-2/3=7/3:4/5=7/3*5/4=35/12
=>x=35/12+2/3=43/12
c: 1/3(x-2/5)=4/5
=>x-2/5=4/5*3=12/5
=>x=12/5+2/5=14/5
d: =>2/3x-1/3-1/4x+1/10=7/3
=>5/12x-7/30=7/3
=>5/12x=7/3+7/30=77/30
=>x=77/30:5/12=154/25
e: \(\Leftrightarrow x\cdot\dfrac{3}{7}-\dfrac{2}{7}+\dfrac{1}{2}-\dfrac{5}{4}x+\dfrac{5}{2}=0\)
=>\(x\cdot\dfrac{-23}{28}=\dfrac{2}{7}-3=\dfrac{-19}{7}\)
=>x=19/7:23/28=76/23
f: =>1/2x-3/2+1/3x-4/3+1/4x-5/4=1/5
=>13/12x=1/5+3/2+4/3+5/4=257/60
=>x=257/65
i: =>x^2-2/5x-x^2-2x+11/4=4/3
=>-12/5x=4/3-11/4=-17/12
=>x=17/12:12/5=85/144
1: x=3/4-1/2=3/4-2/4=1/4
2: x-1/5=2/11
=>x=2/11+1/5=21/55
3: x-5/6=16/42-8/56
=>x-5/6=8/21-4/28=5/21
=>x=5/21+5/6=15/14
4: x/5=5/6-19/30
=>x/5=25/30-19/30=6/30=1/5
=>x=1
5: =>|x|=1/3+1/4=7/12
=>x=7/12 hoặc x=-7/12
6: x=-1/2+3/4
=>x=3/4-1/2=1/4
11: x-(-6/12)=9/48
=>x+1/2=3/16
=>x=3/16-1/2=-5/16
1)x= 1/4
2)x= 2/11+ 1/5
x= 21/55
3)x - 5/6 = 5/21
x = 5/21+5/6
x = 15/14
4)x/5 = 5/6 + -19/30
x:5 = 1/5
x = 1/5.5
x = 1
5) |x| - 1/4 = 6/18
|x| = 6/18 - 1/4
|x| =7/12
⇒x= 7/12 hoặc -7/12
6)x = -1/2 +3/4
x= 1/4
7) x/15 = 3/5 + -2/3
x:15 = -1/15
x = -1/15. 15
x = -1
8)11/8 + 13/6 = 85/x
85/24 = 85/x
⇒ x = 24
9) x - 7/8 = 13/12
x = 13/12 + 7/8
x = 47/24
10)x - -6/15 = 4/27
x = 4/27 + (-6/15)
x = -34/135
11) -(-6/12)+x = 9/48
x= 9/48 - 6/12
x = -5/16
12) x - 4/6 = 5/25 + -7/15
x -4/6 = -4/15
x = -4/15 + 4/6
x = 2/5
Bài 1:
a: \(x=\dfrac{2}{3}:\dfrac{3}{5}=\dfrac{2}{3}\cdot\dfrac{5}{3}=\dfrac{10}{9}\)
b: \(x=\dfrac{17}{8}:\dfrac{7}{17}=\dfrac{17}{8}\cdot\dfrac{17}{7}=\dfrac{289}{56}\)
c: \(x=-\dfrac{3}{4}:\dfrac{7}{12}=\dfrac{-3}{4}\cdot\dfrac{12}{7}=\dfrac{-63}{28}=-\dfrac{9}{4}\)
d: \(\Leftrightarrow x\cdot\dfrac{1}{6}=\dfrac{3}{8}-\dfrac{1}{4}=\dfrac{1}{4}\)
hay \(x=\dfrac{1}{4}:\dfrac{1}{6}=\dfrac{3}{2}\)
e: \(\Leftrightarrow\dfrac{1}{2}:x=-4-\dfrac{1}{3}=-\dfrac{17}{3}\)
hay \(x=-\dfrac{1}{2}:\dfrac{17}{3}=\dfrac{-3}{34}\)
\(4.3^{x-1}+2.3^{x+2}=4.3^6+2.3^9\)
\(3^{x-1}.\left(4+2.3^3\right)=3^6.\left(4+2.3^3\right)\)
\(\Leftrightarrow3^{x-1}=3^6\)
\(\Leftrightarrow x-1=6\)
\(\Leftrightarrow x=7\)
Vậy \(x=7\)
a) \(\dfrac{1}{5}+\dfrac{4}{11}+\dfrac{1}{5}+\dfrac{7}{11}=\dfrac{1}{5}+\left(\dfrac{4}{11}+\dfrac{7}{11}\right)=\dfrac{1}{5}+1=\dfrac{1}{5}+\dfrac{5}{5}=\dfrac{6}{5}\)
b) \(\dfrac{3}{5}\times\dfrac{4}{7}+\dfrac{2}{5}\times\dfrac{4}{7}=\left(\dfrac{3}{5}+\dfrac{2}{5}\right)\times\dfrac{4}{7}=1\times\dfrac{4}{7}=\dfrac{4}{7}\)
a) X + 1/4 = 5/8
b) X - 3/5 = 1/10
c) X x 2/7 = 6/11
d) X : 3/2 = 1/4
đ) 7/4 - X = 5/7
e) 5/4 : x = 1/8
\(a,x+\dfrac{1}{4}=\dfrac{5}{8}\)
\(\Leftrightarrow x=\dfrac{5}{8}-\dfrac{1}{4}\)
\(\Leftrightarrow x=\dfrac{5}{8}-\dfrac{2}{8}\)
\(\Leftrightarrow x=\dfrac{3}{8}\)
\(b,x-\dfrac{3}{5}=\dfrac{1}{10}\)
\(\Leftrightarrow x=\dfrac{1}{10}+\dfrac{3}{5}\)
\(\Leftrightarrow x=\dfrac{1}{10}+\dfrac{6}{10}\)
\(\Leftrightarrow x=\dfrac{7}{10}\)
\(c,x\times\dfrac{2}{7}=\dfrac{6}{11}\)
\(\Leftrightarrow x=\dfrac{6}{11}:\dfrac{2}{7}\)
\(\Leftrightarrow x=\dfrac{6}{11}\times\dfrac{7}{2}\)
\(\Leftrightarrow x=\dfrac{42}{22}\)
\(\Leftrightarrow x=\dfrac{21}{11}\)
\(d,x:\dfrac{3}{2}=\dfrac{1}{4}\)
\(\Leftrightarrow x=\dfrac{1}{4}\times\dfrac{3}{2}\)
\(\Leftrightarrow x=\dfrac{3}{8}\)
\(đ,\dfrac{7}{4}-x=\dfrac{5}{7}\)
\(\Leftrightarrow x=\dfrac{7}{4}-\dfrac{5}{7}\)
\(\Leftrightarrow x=\dfrac{49}{28}-\dfrac{20}{28}\)
\(\Leftrightarrow x=\dfrac{29}{28}\)
\(e,\dfrac{5}{4}:x=\dfrac{1}{8}\)
\(x=\dfrac{5}{4}:\dfrac{1}{8}\)
\(\Leftrightarrow x=\dfrac{5}{4}\times8\)
\(\Leftrightarrow x=\dfrac{40}{4}\)
\(\Leftrightarrow x=10\)
a) \(\dfrac{5}{8}-\left(x+\dfrac{3}{4}\right)=\dfrac{7}{6}\)
\(-x-\dfrac{3}{4}=\dfrac{13}{24}\)
\(-x=\dfrac{31}{24}\)
\(\Rightarrow x=\dfrac{-31}{24}\)
b) \(\left(x-\dfrac{3}{4}\right)+\dfrac{3}{2}=\dfrac{11}{3}\)
\(x-\dfrac{3}{4}=\dfrac{13}{6}\)
\(x=\dfrac{35}{12}\)
c) \(\left(x+\dfrac{1}{2}\right)-\dfrac{5}{8}=2\)
\(x+\dfrac{1}{2}=\dfrac{21}{8}\)
\(x=\dfrac{17}{8}\)
d) \(\dfrac{11}{2}-\left(\dfrac{4}{5}+x\right)=2-\dfrac{1}{3}\)
\(\dfrac{11}{2}-\left(\dfrac{4}{5}+x\right)=\dfrac{5}{3}\)
\(-\dfrac{4}{5}-x=\dfrac{-23}{6}\)
\(-x=\dfrac{-91}{30}\)
\(\Rightarrow x=\dfrac{91}{30}\)
`5/8-(x+3/4)=7/6`
`=> x+3/4 = 5/8 -7/6`
`=> x+3/4 = -13/24`
`=>x= -13/24 -3/4`
`=>x= -13/24 - 18/24`
`=>x= -31/24`
`-----------`
`(x-3/4)+3/2+11/3`
`=11/3` hả bn?
`----------`
`(x+1/2)-5/8=2`
`=>x+1/2=2+5/8`
`=>x+1/2= 16/8+5/8`
`=> x+1/2=21/8`
`=>x=21/8-1/2`
`=>x= 21/8 - 4/8`
`=>x= 17/8`
`---------`
`11/2-(4/5+x)=2-1/3`
`=> 11/2-(4/5+x)=6/3-1/3`
`=> 11/2-(4/5+x)=5/3`
`=>4/5+x=11/2-5/3`
`=>4/5+x=23/6`
`=>x=23/6-4/5`
`=>x= 91/30`